Psychopharmakotherapie bei Demenz und Delir: im Spannungsfeld zwischen Leitlinienempfehlungen und Versorgungspraxis = Treatment with psychotropic agents in patients with dementia and delirium : gap between guideline recommendations and treatment practice - Hewer, Walter; Thomas, Christine (Zeitschrift für Gerontologie und Geriatrie, 2017)
Background and objectives: Psychiatric symptoms in dementia and delirium are associated with a substantially reduced quality of life of patients and their families and often challenging for professionals. Pharmacoepidemiological surveys have shown that, in particular, patients living in nursing homes receive prescriptions of psychotropic agents in significant higher frequency than recommended by current guidelines. This article focuses on a critical appraisal of this gap from the point of view of German healthcare services. Material and methods: Narrative review with special reference to the German dementia guideline from 2016 and recently published practice guidelines for delirium in old age in German and English language. Results: The indications for use of psychotropic agents, especially antipsychotics, are defined narrowly in the German dementia guideline. According to this guideline for several psychopathological symptoms evidence based recommendations cannot be given, currently. For delirium several practice guidelines related to different treatment settings have been published recently. Comparable to the German dementia guideline they recommend general medical interventions and nonpharmacological treatment as first line measures and the use of psychotropic agents only under certain conditions. These guidelines differ to some extent regarding the strength of recommendation for psychopharmacological treatment. Conclusion: The guidelines discussed here advocate well-founded a cautious prescription of psychotropic agents in patients with dementia and delirium. This contrasts to everyday practice which is characterized by significantly higher prescription rates. This gap may explained partially by a lack of evidence-based recommendations regarding certain psychopathological symptoms. Most notably, however, epidemiological data disclose an unacceptable rate of hazardous overtreatment with psychotropic agents, especially in long-term care of persons with dementia. In this situation counteractive measures by consequent implementation of the principles of good clinical practice in geriatrics are required urgently.
Gesehen am 19.09.2018